GAMBARAN BUDAYA KESELAMATAN PASIEN BERDASARKAN METODE AHRQ PADA PEGAWAI RS. ANNA MEDIKA KOTA BEKASI TAHUN 2018 - Deasy Febriyaty; Desyawati Utami (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
This reseach describe the characteristics of patient safety culture with AHRQ method at Anna Medika Hospital Bekasi in 2018. This research was conducted using cross sectional and AHRQ method with 12 dimensions measurement based on Hospital Survey of Patient Safety Culture questionnaire (HSPSC) and assessed the percentage of positive responses from each dimension so as to produce good, medium and less categories. The results of the study mention the description of patient safety culture based on the AHRQ method for hospital employees of Anna Medika Kota Bekasi in 2018 is 71.97%. This data is obtained from the average value of positive response to expectations and actions of superiors in promoting patient safety by 86.79%, positive response to organization learning continuous improvement by 99.79%, positive response to cooperation in units in hospitals by 98,33%, positive response to open communication by 93.14%, positive response to feedback and communication about errors 93.33%, positive response to responses not to blame at 62.42%. Positive response to staffing was 40.29%, positive response to management support for patient safety efforts was 52.40%, positive response to cooperation between units was 60.75%, positive response to shifting shifts and patient transfer was 77.27%, a positive response to the overall perception of patient safety is 79.54%, and a positive response to the frequency of reporting of events is 25.85%.